Faktor-Faktor Yang Mempengaruhi Kemampuan Permodalan dan Pemasaran serta Implikasinya pada Kinerja dan Kesejahteraan Wanita Penerima Bantuan Kelompok Usaha Bersama (KUBE) - Yuce Sariningsih (Kontigensi : Jurnal Ilmiah Manajemen, 2015)
The purpose of this research was obtained empirical evidences and found the intelligibility of the phenomenon of the effect Capital and Marketing Capabilities and Implications on Performance and Women Welfare Recipient Business Group (KUBE).. The research method used descriptive and verification method. The independent variables were : The influence of Creativity, Innovation, and Skills. Capital Capabilities and Marketing Capabilities (Y2)as intervening variable and the dependent variable was Performance and Welfare. SEM analysis was used to examine the models and hypothesis. The results of this study show that: (1) Creativity, Innovation and Skills simultaneously have a significant and positive impact on the ability of capital, (2) Creativity, Innovation and Skills simultaneously have a significant and positive impact on the ability of marketing, (3) Capital and Capabilities Marketing Capabilities have positive influence on the performance of management KUBE;(4) the performance has positive effect on the welfare of KUBE management.